A self-healing PDMS polymer with solvatochromic properties1. Issue 43 (28th May 2015) - Jia, Xiao-Yong; Mei, Jin-Feng; Lai, Jian-Cheng; Li, Cheng-Hui; You, Xiao-Zeng
<x xml:space="preserve">Abstract</x> Cobalt(ii) triazole complexes were incorporated into a polydimethylsiloxane (PDMS) matrix. The resulting polymers show solvent-induced chromic behaviour as well as self-healing properties.